Legal Dissonance and Social Consequences of Unregistered Ṭalāq in Indonesia - Nasrulloh, Muhammad; Ermawan, Mohamad Zakky Ubaid; Thoriquddin, Moh.; Anam, Khoirul (Al-Syakhsiyyah: Journal of Law and Family Studies, 2025)
This study explores the legal dissonance and social consequences arising from the widespread practice of unregistered ṭalāq in Indonesia. It aims to examine the normative conflict between fiqh-based principles and state law, and its implications for husbands, wives, and children. Using normative legal research with a conceptual and descriptive approach, the study finds that unregistered ṭalāq contributes to systemic legal uncertainty and structural inequality, particularly disadvantaging women and children. Legal complications include ambiguous marital status, limitations on remarriage, and procedural obstacles in court and civil registration. Husbands may face the risk of ṭalāq repetition across normative systems, potentially leading to unintended final divorce, alongside repeated obligations related to nafaqah and muṭʿah. Wives face prolonged ʿiddah, abandonment, and disproportionate legal burdens, while children are exposed to psychological distress and a lack of enforceable custodial rights. To address these issues, this paper proposes the institutionalization of ṭalāq validation (isbat ṭalāq) as a harmonizing mechanism between religious and state legal systems, aiming to restore legal certainty, protect vulnerable parties, and promote justice in marital dissolution.